A correlation study on the game of badminton and techniques on shuttlecock durability - Woo, T.; Kootsookos, A.; Alam, F. (Scientific Journal of Sport and Performance, 2024)
Badminton shuttlecocks are often observed to break after several rallies in elite competitions. These change requests are frequent and considered disruptive to the game. The frequency of shuttlecock changes from 36 official matches from the Olympic Games and Super Series between 1997 and 2020 were observed. An Independent T-test and ANOVA were performed on the means of five relevant game characteristics including: format of play by structure (singles vs doubles) and categories (MS, WS, MD, WD and MD), scoring system (pre-2006 vs post-2006), the frequency of badminton shots (smash, attacking shots and rally) that resulted in shuttlecock changes and total time spent on changing shuttlecocks were analysed. The descriptive and frequency analyses found that singles matches resulted in almost 50% more change requests than doubles matches (18.52 ± 8.76 vs 10.73 ± 5.01) and that MS matches were found to have a disproportionately higher number of shuttlecock changes compared to all other categories of play (11.00 vs 3.57 - 4.80 per match). It was also observed that a considerable portion of game time was spent on changes shuttlecock (9.44% - 24.44%). It is believed that addressing shuttlecock durability will reduce disruption due to frequent shuttlecock changes and improve sustainability of the game.